2017
DOI: 10.1158/1078-0432.ccr-16-3227
|View full text |Cite
|
Sign up to set email alerts
|

Germline Mutations in Cancer Susceptibility Genes in a Large Series of Unselected Breast Cancer Patients

Abstract: The prevalence of mutations in cancer susceptibility genes such as and and other cancer susceptibility genes and their clinical relevance are largely unknown among a large series of unselected breast cancer patients in the Chinese population. A total of 8,085 consecutive unselected Chinese breast cancer patients were enrolled. Germline mutations in 46 cancer susceptibility genes were detected using a 62-gene panel. Pathogenic mutations were identified in 9.2% of patients among the 8,085 unselected breast cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
176
8
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 178 publications
(211 citation statements)
references
References 39 publications
24
176
8
3
Order By: Relevance
“…More recently, Sun et al . conducted a monocentric 62‐gene panel sequencing study among 8,085 consecutive unselected Chinese breast cancer patients and reported a similar overall mutation rate of 24.1% in familial breast cancer patients . In another study, Jian et al .…”
Section: Discussionmentioning
confidence: 91%
“…More recently, Sun et al . conducted a monocentric 62‐gene panel sequencing study among 8,085 consecutive unselected Chinese breast cancer patients and reported a similar overall mutation rate of 24.1% in familial breast cancer patients . In another study, Jian et al .…”
Section: Discussionmentioning
confidence: 91%
“…Among these patients, 9,505 were of Chinese Han ethnicity and had had genomic DNA extracted from blood samples of sufficient quantity and quality for BRCA1/2 mutation analysis. Of these 9,505 patients, 8,278 cases were subjected to next‐generation sequencing (NGS) and/or Sanger sequencing for the entire coding regions and exon/intron boundaries of the BRCA1 and BRCA2 genes. The remaining 1,227 cases were sequenced for recurrent pathogenic variants of BRCA1/2 genes using Sanger sequencing .…”
Section: Methodsmentioning
confidence: 99%
“…The remaining 1,227 cases were sequenced for recurrent pathogenic variants of BRCA1/2 genes using Sanger sequencing . The applied method of mutation screening was described in detail in our previous report . Each pathogenic variant was double‐confirmed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…We had previously recruited a total of 10,378 consecutive breast cancer patients treated at the Breast Center of Peking University Cancer Hospital (Beijing, China) from October 2003 to May 2015, of whom 8,085 received multi‐gene panel sequencing, as described in our previous study . That study showed that 428 (5.3%) patients carried a germline mutation in BRCA1 or BRCA2 . Therefore, 7,657 non‐ BRCA1/2 mutant patients were included in the present study.…”
Section: Methodsmentioning
confidence: 99%
“…The panel covered all RAD50 coding regions and splice sites. Sequencing was performed on a HiSeq 2500 platform (Illumina Inc., San Diego, CA) as described in our previous study . All pathogenic mutations were validated by independent PCR and Sanger sequencing.…”
Section: Pathologymentioning
confidence: 99%